Treatment of Spider Phobia Using Repeated Exposures and Adjunctive Repetitive Transcranial Magnetic Stimulation: A Proof-of-Concept Study - Leuchter, Michael K.; Rosenberg, Benjamin M.; Schapira, Giuditta; Wong, Nicole R.; Leuchter, Andrew F.; McGlade, Anastasia L.; Krantz, David E.; Ginder, Nathaniel D.; Lee, Jonathan C.; Wilke, Scott A.; Tadayonnejad, Reza; Levitt, Jennifer; et al. (Frontiers in Psychiatry, 2022)
Background Specific phobias represent the largest category of anxiety disorders. Previous work demonstrated that stimulating the ventromedial prefrontal cortex (vmPFC) with repetitive Transcranial Magnetic Stimulation (rTMS) may improve response to exposure therapy for acrophobia. Objective To examine feasibility of accelerating extinction learning in subjects with spider phobia using intermittent Theta Burst Stimulation (iTBS) rTMS of vmPFC. Methods In total, 17 subjects with spider phobia determined by spider phobia questionnaires [Spider Phobia Questionnaire (SPQ) and Fear of Spiders questionnaire (FSQ)] underwent ratings of fear of spiders as well as behavioral and skin conductance data during a behavioral avoidance test (BAT). Subjects then received a sequential protocol of in vivo spider exposure followed by iTBS for three sessions administered to either active or control treatment sites (vmPFC [n = 8] or vertex [n = 9], respectively), followed 1 week later by repetition of questionnaires and BAT. Results All subjects improved significantly regardless of group across both questionnaires (FSQ η2 = 0.43, p = 0.004; SPQ η2 = 0.39, p = 0.008) and skin conductance levels during BAT (Wald χ2 = 30.9, p < 0.001). Subjects in the vmPFC group tolerated lower treatment intensity than in the control group, and there was a significant correlation between treatment intensity, BAT subjective distress improvement, and physiologic measures (all ρ > 0.5). Conclusion This proof-of-concept study provides preliminary evidence that a sequential exposure and iTBS over vmPFC is feasible and may have rTMS intensity-dependent effects on treatment outcomes, providing evidence for future areas of study in the use of rTMS for phobias.